2002
DOI: 10.1093/clinchem/48.12.2242
|View full text |Cite
|
Sign up to set email alerts
|

Stability Studies of Twenty-Four Analytes in Human Plasma and Serum

Abstract: Background: The stability and stoichiometric changes of analytes in plasma and serum after prolonged contact with blood cells in uncentrifuged Vacutainer® tubes were studied. Methods: We simultaneously investigated the stability of 24 analytes (a) after prolonged contact of plasma and serum with blood cells and (b) after immediate separation of plasma and serum (centrifuged twice at 2000g for 5 min). We verified biochemical mechanisms of observed analyte change by concomitant measurement of pH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
125
5
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(146 citation statements)
references
References 13 publications
12
125
5
4
Order By: Relevance
“…The linear decrease in plasma ctCO2 over time and the faster rate of decrease in plasma ctCO2 in the DC group most likely reflected prolonged contact time with leucocytes, erythrocytes and platelets. This result was consistent with those of 3 previous studies of human serum or plasma samples [9,10,12]. Storage of human serum or plasma samples in contact with blood cells at 25°C resulted in a significant decrease in ctCO2 after 56 h, with a faster rate of decline noted in plasma samples [12].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The linear decrease in plasma ctCO2 over time and the faster rate of decrease in plasma ctCO2 in the DC group most likely reflected prolonged contact time with leucocytes, erythrocytes and platelets. This result was consistent with those of 3 previous studies of human serum or plasma samples [9,10,12]. Storage of human serum or plasma samples in contact with blood cells at 25°C resulted in a significant decrease in ctCO2 after 56 h, with a faster rate of decline noted in plasma samples [12].…”
Section: Discussionsupporting
confidence: 92%
“…This result was consistent with those of 3 previous studies of human serum or plasma samples [9,10,12]. Storage of human serum or plasma samples in contact with blood cells at 25°C resulted in a significant decrease in ctCO2 after 56 h, with a faster rate of decline noted in plasma samples [12]. In addition, serum cHCO3 decreased by 4 mmol/l when human serum samples in contact with blood were stored for 24 h at 30, 32 and 37°C [9,10].…”
Section: Discussionsupporting
confidence: 91%
“…We showed that CO 2 mean concentration decreases progressively in heparinized plasma, remaining stable up to 4 hr (mean bias -12.4%; ACL 15.4%), and then decreases significantly (mean bias -19.7% at +6 hr). Boyanton and Blick did not show any significant decrease in CO 2 in plasma up to 56 hr of storage at 25°C (greatest change -4.8%), neither did Oddoze et al up to 4 hr (-0.8%) (5,6). Nevertheless, in accordance with our result, Doumas et al also observed a growing decrease in plasma bicarbonate stored in capped original tubes (from -7% to -19% between +4 and +24 hr of storage) (10).…”
Section: Stability In Plasmamentioning
confidence: 78%
“…Stahl et al found negligible variations of stability in whole blood at 23°C for LDH (-3.3%, -5.5%, -1.3% at 2, 4, and 6 hr, respectively) and for K (-2.6%, -0.5%, -3.1% at 2, 4, and 6 hr, respectively) (12). Boyanton and Blick did not show any significant variation of stability for LDH and K after 4 and 8 hr, except a slight decrease in K concentration (-0.1 mmol/l) at 4 hr (6). Nonetheless, one must remember that stability of LDH and K depends on the temperature, which is known to influence enzymatic activities (13).…”
Section: Stability In Whole Bloodmentioning
confidence: 86%
See 1 more Smart Citation